The haemodynamic basis of lung congestion during exercise in heart failure with preserved ejection fraction. (14th October 2019) - Reddy, Yogesh N V; Obokata, Masaru; Wiley, Brandon; Koepp, Katlyn E; Jorgenson, Caitlin C; Egbe, Alexander; Melenovsky, Vojtech; Carter, Rickey E; Borlaug, Barry A
Abstract: Aims : Increases in extravascular lung water (EVLW) during exercise contribute to symptoms, morbidity, and mortality in patients with heart failure and preserved ejection fraction (HFpEF), but the mechanisms leading to pulmonary congestion during exercise are not well-understood. Methods and results : Compensated, ambulatory patients with HFpEF ( n = 61) underwent invasive haemodynamic exercise testing using high-fidelity micromanometers with simultaneous lung ultrasound, echocardiography, and expired gas analysis at rest and during submaximal exercise. The presence or absence of EVLW was determined by lung ultrasound to evaluate for sonographic B-line artefacts. An increase in EVLW during exercise was observed in 33 patients (HFpEFLW+, 54%), while 28 (46%) did not develop EVLW (HFpEFLW− ). Resting left ventricular function was similar in the groups, but right ventricular (RV) dysfunction was two-fold more common in HFpEFLW+ (64 vs. 31%), with lower RV systolic velocity and RV fractional area change. As compared to HFpEFLW−, the HFpEFLW+ group displayed higher pulmonary capillary wedge pressure (PCWP), higher pulmonary artery (PA) pressures, worse RV-PA coupling, and higher right atrial (RA) pressures during exercise, with increased haemoconcentration indicating greater loss of water from the vascular space. The development of lung congestion during exercise was significantly associated with elevations in PCWP and RA pressure as well as impairments in RV-PA coupling (area under the curve values 0.76–0.84). Conclusion : Over half of stable outpatients with HFpEF develop increases in interstitial lung water, even during submaximal exercise. The acute development of lung congestion is correlated with increases in pulmonary capillary hydrostatic pressure that favours fluid filtration, and systemic venous hypertension due to altered RV-PA coupling, which may interfere with fluid clearance. Clinical trial registration : NCT02885636.